Digital Transformation In Handling Sexual Violence In Higher Education Institutions - Heliany, Ina; Windiyastuti , Feny; Laela, Sofa (Dinasti Research, 2025)
This study aims to analyze the implementation of digital transformation in addressing sexual violence cases within higher education institutions by emphasizing the role of protection and assistance task forces through a feminist policy perspective. The research employed a descriptive qualitative method with data collection techniques including in-depth interviews, observations, and document reviews. The data were analyzed using a thematic approach to identify patterns, challenges, and opportunities for strengthening digital-based reporting and assistance mechanisms. The findings indicate that the existence of digital reporting systems contributes to improved accessibility and confidentiality for victims, yet still faces obstacles in terms of outreach, human resources, and technological sustainability. The role of the task force is proven to be crucial in ensuring victim-centered assistance, although capacity building and institutional support remain necessary for optimal system performance. Overall, digital transformation has the potential to serve as a strategic instrument in creating a safe, just, and responsive college environment for victims.